Islamic Educational Values within the Tialo Tribe Marriage Tradition in Tomini District - Fatun Nisya; Adawiyah Pettalongi; Erniati; Andi Anirah (Journal of Education and Teaching Learning, 2026)
This research was motivated by the sustainability of the Tialo Tribe wedding tradition in Tomini District as a cultural heritage practiced in harmony with Islamic teachings and containing educational values. The research aimed to describe the Tialo wedding tradition, examine the stages of implementation, and analyze the values of Islamic education contained in it. The research used a descriptive qualitative method in Tomini District, Parigi Moutong Regency, with data obtained through observation, interviews, and documentation. Informants were selected through purposive sampling involving traditional leaders, religious leaders, heads of KUA, village heads, and community leaders. Data analysis were carried out through data reduction, data presentation, and conclusion while data validity was ensured through triangulation and member check. The results of the research show that the Tialo Tribe wedding tradition is a cultural system that integrates Islamic customs and values through ideas, social activities, and cultural symbols. This tradition is carried out through the pre-marriage, marriage contract, and post-marriage stages involving active community participation. The values of Islamic education contained include the values of faith, worship, morals, and social which are reflected in belief in Allah, the implementation of worship, respect for parents, responsibility, deliberation, mutual cooperation, solidarity, and friendship.